Low-leakage kV-class GaN vertical p–n diodes with non-destructive breakdown enabled by hydrogen-plasma termination with p-GaN extension. (7th June 2021) - Yang, Chen; Fu, Houqiang; Fu, Kai; Yang, Tsung-Han; Zhou, Jingan; Montes, Jossue; Zhao, Yuji
Abstract: This paper demonstrates low-leakage hydrogen plasma (HP) terminated GaN-on-GaN vertical p–n diodes. The leakage current was decreased by ∼800 times (at −600 V), and the breakdown voltage was nearly doubled with a p-GaN extension design. The devices showed a non-destructive breakdown voltage of 1.68 kV, a specific on-resistance ( R on ) of 0.40 MΩ cm 2, and a Baliga's figure of merit of 7.1 GW cm −2 . These results indicate that HP termination with p-GaN extension is effective in reducing leakage and enhancing the breakdown capability of vertical GaN power diodes.